Study on Temperature Rise Characteristics of Grease Lubricated Thrust Angular Contact Ball Bearings Under Complex Working Conditions - Shijie Wang; Pengchang Jiang; Feng Liu; Guixiu Luo; Zhanli Zhang (Jixie chuandong)
The temperature rise characteristics of grease lubricated angular contact ball bearings under complex working conditions have an important influence on the safe operation of bearings. The temperature rise characteristics of the grease lubricated thrust angular contact ball bearings under complex working conditions are studied； a mathematical model of friction heating rate of thrust angular contact ball bearings is established； based on heat transfer theory， the heat transfer mode of spindle-bearing-bearing block system is analyzed， the temperature rise model of bearing is established and the rationality of the model is verified by experiments. Based on the temperature rise model of bearings， the influence of bearing operating working parameters and structural parameters on the temperature rise characteristics of bearing outer ring is analyzed. The results show that the established model can predict the temperature rise of bearing outer ring under complex working conditions well； the maximum error between the simulation results and the test results is 8.3%； the temperature rise rate of the outer ring of the bearing is faster within 20 minutes after the start of the bearing operation； the load， speed and ambient temperature increased will increase the temperature rise of the outer ring of the bearing； the number of steel balls and groove curvature radius coefficient increased will decrease the temperature rise of bearing outer ring. The research results provide a theoretical basis for optimal design of thrust angular contact ball bearings with grease lubrication.